2021
DOI: 10.1080/07421656.2021.1957341
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory fNIRS Assessment of Differences in Activation in Virtual Reality Visual Self-Expression Including With a Fragrance Stimulus

Abstract: A within-subjects experimental design examined differences in functional near-infrared spectroscopy (fNIRS) assessment of prefrontal cortex (PFC) activation with two virtual reality (VR) drawing conditions (rote tracing and creative self-expression) with and without a fragrance stimulus. Participants were healthy adults and included 18 women, 6 men: age range ¼ 18-54 years. Findings indicate significant differences such that rote tracing resulted in higher PFC activity than the creative self-expression task. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 44 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…The recent development of in-house custom systems for odor research has also shown a tendency toward low channel density, as in the case of Moein et al ( 2020 ) and Chen et al ( 2021 ). The need to combine fNIRS with other wearable systems, particularly virtual reality headsets, may also contribute to lower channel numbers (Kaimal et al, 2021 ). It should be noted that six studies did not report channel density information, so were excluded from Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recent development of in-house custom systems for odor research has also shown a tendency toward low channel density, as in the case of Moein et al ( 2020 ) and Chen et al ( 2021 ). The need to combine fNIRS with other wearable systems, particularly virtual reality headsets, may also contribute to lower channel numbers (Kaimal et al, 2021 ). It should be noted that six studies did not report channel density information, so were excluded from Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…fresh flower petals, collected on the day of testing as a stimulus, allowing the odor to diffuse into the air within a pressure container. Five studies implemented odor delivery mechanisms aiming to diffuse odor into the environment around the participant, including below the participants nose with the use of a wearable odor tray (Onuma and Sakai, 2018 ; Song et al, 2019 ; Tomono and Tomono, 2020 ; Kaimal et al, 2021 ; Tomono et al, 2021 ). One of these studies, Tomono and Tomono ( 2020 ) expelled odor vapor via a airflow generator toward the participant, whilst also measuring odor concentration produced to check odor concentration consistency ( Figure 11d ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations